Minority Success in Non-Majority Minority Districts: Finding the "Sweet Spot". (July 2020) - Lublin, David; Handley, Lisa; Brunell, Thomas L.; Grofman, Bernard
Abstract: Though African-American and Latino electoral success in state legislative and congressional elections continues to occur almost entirely in majority-minority districts, minorities now have new opportunities in districts that are only 40–50% minority. This success can primarily be explained in terms of a curvilinear model that generates a "sweet spot" of maximum likelihood of minority candidate electoral success as a function of minority population share of the district and the proportion of the district that votes Republican. Past racial redistricting legal challenges often focused on cracking concentrated racial minorities to prevent the creation of majority-minority districts. Future lawsuits may also follow in the steps of recent successful court challenges against racially motivated packing that resulted in the reduction of minority population percentage in a previously majority-minority district in order to enhance minority opportunity in an adjacent non-majority-minority district.